Persepsi Tenaga Kesehatan dan Manajemen Penanganan Pre-eklampsia Dalam Kehamilan : Scoping Review - Rafhani Rosyidah; Alfisyar Agmar; Siti Cholifah (Jurnal Ilmiah Kesehatan, 2025)
Preeclampsia is a major pregnancy complication that significantly contributes to maternal and fetal morbidity and mortality, requiring timely and competent management by healthcare professionals. Healthcare providers’ perceptions, knowledge, and clinical practices play a crucial role in the early detection and management of preeclampsia; however, primary studies addressing these aspects remain limited. This article presents a scoping review aimed at exploring healthcare professionals’ perceptions and management practices in preeclampsia during pregnancy. A systematic literature search was conducted across four major databases—PubMed, Springer, ScienceDirect, and EBSCOhost—covering studies published between 2019 and 2024, including quantitative and qualitative research in English and Indonesian, with article selection guided by PRISMA guidelines. Data were extracted using Microsoft Excel and synthesized descriptively. Of the 314 articles identified, six met the inclusion criteria, all conducted in African countries. The findings indicate considerable variation in healthcare professionals’ perceptions, levels of knowledge, and clinical practices regarding preeclampsia, particularly among midwives, influenced by clinical experience and training. These variations may affect the quality of preeclampsia management and maternal healthcare services.